Transforming Education: A Review of the Impact of the TPR Method on Learning English as a Second Language: Transformar la educación: una revisión del impacto del método respuesta física total en el aprendizaje del inglés como segunda lengua (Papeles, 2025)
Introduction: What is the impact of the Total Physical Response (TPR) method on the acquisition of language skills in ESL students? The use of TPR using physical commands linked to linguistic concepts has been found to facilitate students’ retention, comprehension, and motivation when learning a new language, contributing to a more natural and less stressful experience. Methodology: A total of 80 previous studies were found, and 55 were reviewed qualitatively, located in Elsevier, Google Scholar, Scielo, ScienceDirect and ResearchGate, such review consisted in the collection and analysis of data about the application of the method, highlighting as results the effectiveness and possible challenges that may arise. The studies were classified according to the categories of “English at an early age”, “Language acquisition using the TPR method”, “English in adolescents”, “Development of macro skills”, and “TPR as a methodological strategy”. Results: The results of the literature review showed that the TPR method is effective in the early stages of learning English because it allows direct association between words and actions, which increases retention and decreases anxiety, but it also has certain limitations for students at advanced levels. Discussion: The TPR method has a positive impact on the learning of English as a second language, since it facilitates vocabulary acquisition and promotes a dynamic and motivating environment, even so, a balanced implementation of TPR together with other methods that complement learning at different or advanced levels is suggested.
Keywords: Total Physical Response; learning; Dynamic environment; positive impact; ESL